Studi Kualitatif Dampak Uji Kompetensi Dokter Indonesia terhadap Pembelajaran pada Mahasiswa Kedokteran - Firmansyah, Marindra; Widyandana, Widyandana; Rahayu, Gandes Retno (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: There are two important characteristics that need to be considered by the institution of medical education today, the first is about the importance of using assessment as a measuring instrument and the role of curriculum in producing good quality graduates. UKDI is only one exit to be a doctor that will certainly have varied impact on students from the expected and unexpected. The purpose of this study was to determine the impact on student learning UKDI on which will follow UKDI related to the allocation of time for study, the number of hours of study, the distribution of learning, the selection of learning resources and learning materials selection.Method: The research method is qualitative study that use Focus Group Discussion to get the data. The number of participants is 61 people devided into 6 groups. That group of students at the Faculty of Medicine with the accreditation of A, B and C respectively - each of the public and private colleges.Results: The results of the qualitative analysis portrait that UKDI has an impact on the student learning. The impact of learning that occurs associated with two things, the first is related to the quality of student learning and the second related to student metacognitive regulation. The general quality of the student learning that occurs in the face of UKDI is still low quality, learn by rote. For metacognitive regulation is related to the allocation, the number and distribution of learning, the selection of learning materials, the selection of learning resources, the selection of a place of learning, learning strategies, learning to maintain consistency, and monitor the process of learning and improvement.Conclusion: UKDI have an impact on the learning of medical students, both in the quality of learning and metacognitive regulation.